Vicious and Good/Virtuous Relationships in the Teachings of the Church Fathers - Artemi, Eirini (European Scientific Journal, ESJ, 2022)
Christ brought a rebellion to human life according to religious and ethical orders. Christians should put these orders into practice in their daily life. Christian ethics emphasized that morality should unite with Christ and Church’s sacred mysteries, otherwise it was not worthy. The central feature of Byzantine culture was Orthodox Christianity. Christian Ethics in the Byzantine Empire was not a systematic philosophical discipline but an occasional response to particular problems posed in everyday life or interpreting the Scripture. The Christian law and the Church commandments were set within the context of devotion to God but were deontological standards defining what this morality was. The highest ethical duty of a Christian was the same as the greatest commandment: love God and love your neighbor. In this paper, we are going to search for vicious and good/virtuous relationships in the teachings of the Church Fathers based on the social structure and gender relations in the Byzantine state and mainly on spouses’ relations. Which was the attitude of the Church Fathers to the specific topic in the Byzantine era? Did they dare to criticize vicious actions among people like adultery, homosexuality, prostitution, and concubinage? Which was their influence on the laws of the Byzantine Empire about the status of marriage? How did they present the virtuous relations as religious attitudes against vicious actions which help the social life of married and unmarried Christians and their sexual life?